The Role of High-Fidelity Team-Based Simulation in Acute Care Settings: A Systematic Review - Armenia, Sarah; Thangamathesvaran, Loka; Caine, Akia D.; King, Neil; Kunac, Anastasia; Merchant, Aziz M. (The Surgery Journal, 2018)
Introduction High-fidelity team-based simulation has been identified as an effective way of teaching and evaluating both technical and nontechnical skills. Several studies have described the benefits of this modality in a variety of acute care settings, but a lack of standardized methodologies has resulted in heterogeneous findings. Few studies have characterized high fidelity simulation across a broad range of acute care settings and integrated the latest evidence on its educational and patient impact.Methods The MEDLINE, EMBASE, Cochrane Library, and PsycINFO databases were searched for empirical studies from the last 10 years, investigating high fidelity team-based simulation in surgical, trauma, and critical care training curricula.Results Seventeen studies were included. Interventions and evaluations were comprehensively characterized for each study and were discussed in the context of four overarching acute care settings: the emergency department/trauma bay, the operating room, the intensive care unit, and inpatient ad hoc resuscitation teams.Conclusions The use of high-fidelity team-based simulation has expanded in acute care and is feasible and effective in a wide variety of specialized acute settings, including the emergency department/trauma bay, the operating room, the intensive care unit, and inpatient ad hoc resuscitation teams. Training programs have evolved to emphasize team-based, multidisciplinary education models and are often conducted in situ to maximize authenticity. In situ simulations have also provided the opportunity for system-level improvement and discussions of complex topics such as social hierarchy. There is limited evidence supporting the impact of simulation on patient outcomes, sustainability of simulation efforts, or cost-effectiveness of training programs. These areas warrant further research now that the scope of utilization across acute care settings has been characterized.
Keywords: teaching; simulation training; team training; high fidelity simulation training; education; simulation-based medical education